Association of Pathogenic Th17 Cells with the Disease Severity and Its Potential Implication for Biological Treatment Selection in Psoriasis Patients. (31st July 2020) - Aguilar-Flores, Cristina; Castro-Escamilla, Octavio; Ortega-Rocha, Elizabeth M.; Maldonado-García, César; Jurado-Santa Cruz, Fermín; Pérez-Montesinos, Gibrán; Lemini-López, Alicia; Bonifaz, Laura C.
Abstract : Psoriasis is an inflammatory autoimmune disease characterized by cutaneous lesions in plaques. It has been proposed that the immune response has a key role in the disease progression. Particularly, the Th17 cells through IL-17 can contribute to maintain the inflammatory process. The pathogenic Th17 phenotype has been described in human diseases and associated with high severity in inflammatory experimental models. However, it is not clear if the pathogenic phenotype could be present in the skin and peripheral blood as well as its possible association to severity in psoriasis. In the lesional skin, we found high infiltration of Th17 cells and the pathogenic phenotype, finding a correlation between the frequency of Th17 cells and the Psoriasis Area and Severity Index (PASI) score. In peripheral blood, we observed a pool of Th17 lymphocytes with potential to acquire pathogenic features. Interestingly, the percentage of pathogenic Th17 cells (CD4 + ROR γ t + IFN- γ + ) correlates with disease severity. Moreover, we distinguished three groups of patients based on their IL-17/IFN- γ production by Th17 lymphocytes, which seems to be related with a dynamic or stable potential to express these cytokines. Remarkably, we evaluated the cytokine production by Th17 cells as an immunological marker for the adequate selection of biologic therapy. We found that patients analyzed by this immunological approach and treated with antibodies against IL-17 and TNF α showed great improvement depicted by reduction in PASI and Dermatology Life Quality Index (DLQI) score as well as the percentage of Body Surface Area (BSA). Altogether, our results highlight the importance of the assessment of the pathogenic phenotype in Th17 cells as an immune personalized analysis with the potential to support the therapy choice in the clinical practice.